IMPLEMENTASI KONSEP INTEGRASI SAINS-ISLAM PADA PROGRAM OLIMPIADE DALAM MEMBENTUK KARAKTER UNGGUL SISWA MAN 2 MALANG - Fatnun Fajriyah; Imron Rossidy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was conducted in response to the challenges of modern education that tend to prioritize academic achievement without adequately strengthening students’ religious character and leadership values. The dichotomy between science and religion is considered to contribute to the weakening of students’ moral awareness, making it necessary to examine educational models that integrate science and Islam holistically. This research aims to analyze the implementation of the science-Islam integration concept in the Insan Pro Olympic and research program at MAN 2 Kota Malang and its implications for the formation of students’ superior character. The study employed a qualitative approach with a field research design. Data were collected through participatory observation, in-depth interviews with the head of the Insan Pro program and Olympic students, as well as documentation of religious and academic activities. The collected data were analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings reveal that the integration of science and Islam is implemented conceptually through the madrasah’s vision, mission, goals, and institutional culture, and practically through the habituation of religious activities such as congregational prayer, Qur’anic recitation, Quzido (Qur’an, dhikr, and prayer), tausiyah, tahajud prayer, and Islamic motivation sessions within the Olympic coaching process. This integration contributes to the development of superior character traits among students, including religiosity, discipline, responsibility, social awareness, honesty, and leadership with noble morals. The study concludes that the consistent integration of science and Islamic values can serve as an effective model for balancing academic excellence and character education in madrasah environments.